2009
DOI: 10.1093/glycob/cwp149
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of GD3 ganglioside as a novel biomarker of mouse neural stem cells

Abstract: Neural stem cells (NSCs) are undifferentiated neural cells characterized by their high proliferative potential and the capacity for self-renewal with retention of multipotency. Over the past two decades, there has been a huge effort to identify NSCs morphologically, genetically, and molecular biologically. It is still controversial, however, what bona fide NSCs are. To define and characterize NSCs more systematically, it is crucial to explore novel cell-surface marker molecules of NSCs. In this study, we focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
83
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 37 publications
1
83
0
Order By: Relevance
“…NPCs retain stem cell characteristics, including a high proliferative potential and the ability to selfrenew [30]. In this study, we identified Sur8, the scaffold protein of the Ras-ERK pathway [6][7][8], as a factor that maintains self-renewal capacity and the undifferentiated state in NPCs.…”
Section: Discussionmentioning
confidence: 99%
“…NPCs retain stem cell characteristics, including a high proliferative potential and the ability to selfrenew [30]. In this study, we identified Sur8, the scaffold protein of the Ras-ERK pathway [6][7][8], as a factor that maintains self-renewal capacity and the undifferentiated state in NPCs.…”
Section: Discussionmentioning
confidence: 99%
“…In later developmental stages, however, more complex gangliosides prevail, particularly GM1 (GalĪ²1-3GalNAcĪ²1-4(NeuAcĪ±2-3)GalĪ²1-4GlcĪ²1-1ā€²Cer), GD1a (NeuAcĪ±2-3GalĪ²1-3GalNAcĪ²1-4(NeuAcĪ±2-3)GalĪ²1-4GlcĪ²1-1ā€² Cer), GD1b (GalĪ²1-3GalNAcĪ²1-4(NeuAcĪ±2-8NeuAcĪ±2-3) GalĪ²1-4GlcĪ²1-1ā€²Cer), and GT1b (NeuAcĪ±2-3GalĪ²1-3GalNAcĪ²1-4 (NeuAcĪ±2-8NeuAcĪ±2-3)GalĪ²1-4GlcĪ²1-1ā€²Cer) (2,3). Because of the spatiotemporal expression patterns, gangliosides abundant in embryonic brain, such as GD3 and the c-series ganglioside antigen marker A2B5, have been considered to be useful stage-specific markers of early brain development (4,5). Mounting evidence supports the notion that gangliosides serve regulatory roles in neurogenesis through modulating processes, such as intercellular recognition, interaction, adhesion, reception, and/ or signaling (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…In primary NSCs prepared from mice, the expression of GD3 was found to coexist with that of stage-specific embryonic antigen 1, another mouse NSC marker, in cultured neurospheres and neuroepithelial cells (NECs), but not in differentiated cells. For that reason, GD3 can be considered a useful NSC surface marker (4). The specific expression of GD3 in NSCs and its dynamic change during neural development prompted us to investigate the functional role of GD3 in regulating NSC fate determination.…”
mentioning
confidence: 99%
“…NSC Culture-NSCs were prepared in the form of neurospheres according to methods described previously (22,24). In brief, single cell suspensions prepared from the striata of ICR mouse embryos (embryonic day 14.5) were cultured in Neurobasal-A medium (Invitrogen) containing B27 serum-free supplement (Invitrogen), L-glutamine (Invitrogen), 20 ng/ml basic FGF (PeproTech, Rocky Hill, NJ), and 20 ng/ml of epidermal growth factor (EGF; PeproTech).…”
Section: Methodsmentioning
confidence: 99%